Electrospun hollow nanofibers for advanced secondary batteries. (September 2017) - Li, Linlin; Peng, Shengjie; Lee, Jeremy Kong Yoong; Ji, Dongxiao; Srinivasan, Madhavi; Ramakrishna, Seeram
Abstract: Electrospinning is a versatile and efficient technique to fabricate hollow structured nanofibers of metal oxides, carbon, metals, composites, and others, which present great potential in energy conversion and storage devices. In this review, we provide a comprehensive overview of the preparation of electrospun inorganic hollow nanofibers and their applications in advanced secondary batteries. We first describe different synthetic methodologies for fabricating hollow nanofibers as well as the compositional and geometric manipulation of these nanofibers based on electrospinning. We next go on to discuss the recent research activities involving electrospun hollow nanofibers in advanced secondary batteries, including lithium-ion batteries, sodium-batteries, Li-S batteries, and metal-air batteries. In each application, some typical examples and a critical commentary are provided to demonstrate the superior properties of the hollow structures. The correlation between geometric properties of hollow structures and their performance are also highlighted. These results demonstrate that electrospun hollow nanofibers with unique properties such as large surface area, engineered high porosity, and free-standing characteristics have a direct impact on the final performance in their applications. Finally, in conclusion, the remaining challenges of adopting electrospun hollow nanofiber materials in their future applications are further discussed. Graphical abstract: The review summarizes the recent progress of the preparation of electrospun inorganic hollow nanofibers and their applications in advanced secondary batteries, including lithium-ion batteries, sodium-batteries, Li-S batteries, and metal-air batteries. Highlights: The present advanced secondary batteries are reviewed. The synthesis of electrospun nanofibers is emphasized. The relationship between the structures and performance is discussed. The remaining challenges are suggested as well.